The trauma in contemporary Arabic poetry: Muhammad al-Maghout and Mahmoud Darwish as models - Nasr , Dorine Nabil; Merhi, Nermine Majed (Research Journal in Advanced Humanities, 2025)
This academic paper explores the concept of "Trauma" in contemporary Arabic poetry, showing a critical perspective on how literature reflecting human experience is read. Trying to decode the textual elements that reveal the impact of Trauma in the collection of the Syrian poet Muhammad al-Maghout and the Palestinian poet Mahmoud Darwish. The research also aims the psychological effects in the discourse of these poets, by focusing on their choice of the event that consequently Empowered the reader’s awareness of trauma, particularly the one reading al-Maghout’s and Darwish’s poetry in other languages.We have decided to adopt the descriptive analytical approach to address this research, as the analytical approach is based on the theory of Trauma criticism and its literature, based on the theories of Cathy Caruth, in addition to the connection of this approach with postcolonial theory, cultural criticism, and psychoanalysis.The research achieves with various findings, determined by observing the representations of Trauma in the works of the two poets featured in this study. Where psychological disorders manifested in their works caused by the recollection of traumatic events, including torture and killing, as well as memories related to childhood.